The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/pharmaceutics15061750
|View full text |Cite
|
Sign up to set email alerts
|

Toward a New Generation of Bio-Scaffolds for Neural Tissue Engineering: Challenges and Perspectives

Francisca Villanueva-Flores,
Igor Garcia-Atutxa,
Arturo Santos
et al.

Abstract: Neural tissue engineering presents a compelling technological breakthrough in restoring brain function, holding immense promise. However, the quest to develop implantable scaffolds for neural culture that fulfill all necessary criteria poses a remarkable challenge for material science. These materials must possess a host of desirable characteristics, including support for cellular survival, proliferation, and neuronal migration and the minimization of inflammatory responses. Moreover, they should facilitate el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 178 publications
0
5
0
Order By: Relevance
“…The mechanical properties of scaffolds are essential for neural tissue engineering, as the brain is the softest organ in the body. Scaffolds must mimic the mechanical properties of the brain with adequate stiffness to allow for cell attachment [ 18 ]. For example, the mechanical stress experienced by the neuronal membrane along the scaffold surface interface dictates axonal growth and directionality [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The mechanical properties of scaffolds are essential for neural tissue engineering, as the brain is the softest organ in the body. Scaffolds must mimic the mechanical properties of the brain with adequate stiffness to allow for cell attachment [ 18 ]. For example, the mechanical stress experienced by the neuronal membrane along the scaffold surface interface dictates axonal growth and directionality [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Topography is crucial in favoring neurite attachment. For example, nanostructured surfaces that mimic the architecture of the extracellular matrix can favor cell propagation, proliferation, adhesion, neurite extension and branching, migration, and electrical signal transmission, while topography influences neural stem cell differentiation [ 18 ]. Previous studies have shown that neural cells can align and elongate in the direction of aligned nanofibers more clearly than those grown on random nanofibers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations